PRODUCTIVITY OF SOYBEAN VARIETIES BASED ON SEEDING RATE IN THE WESTERN FOREST-STEPPE - Bliatnyk , Т. (Bulletin of Lviv National Environmental University. Series Agronomy, 2025)
This study presents research findings on the impact of seeding rate on the formation of individual yield components and overall biological productivity of soybean varieties cultivated in the Western Forest-Steppe. The research was conducted during the 2023–2024 growing seasons at the “Zakhidnyi Buh” private enterprise, located in the village of Shymkivtsi, Ternopil district, Ternopil region. The field experiment included three soybean varieties: Abelina, Kyoto, and Akardia, with five different seeding rates ranging from 400 to 900 thousand seeds per hectare applied to each variety. The results indicated that the individual productivity of each plant and the biological yield of soybean varieties changed depending on the seeding rates. Specifically, as the seeding rate increased from 400 to 900 thousand seeds per hectare, the number of beans and seeds per plant decreased. Over two years of research, the average number of beans per plant was recorded as follows: the Abelina variety had between 15.6 and 19.8 beans per plant, the Kyoto variety had between 16.5 and 21.9 beans, and the Akardia variety had between 16.0 and 21.7 beans. Furthermore, increasing the seeding rate from 500 to 900 thousand seeds per hectare resulted in a decrease in the number of seeds per plant compared to the minimum seeding rate. For the Abelina variety, the decrease was between 3.0 and 15.0 seeds, for the Kyoto variety it was between 4.6 and 30.0 seeds, and for the Akardia variety, it was between 5.4 and 21.3 seeds. The research noted that the highest biological yield for the early varieties, Abelina and Akardia, was achieved with a seeding rate of 700 thousand seeds per hectare, resulting in yields of 3.86 and 4.39 tons per hectare, respectively. This exceeded the minimum yield by 0.71 and 0.35 tons per hectare. For the mid-early variety, Kyoto, optimal productivity was attained with a seeding rate of 600 thousand seeds per hectare, yielding 4.53 tons per hectare, which was an increase of 0.40 tons per hectare. Further increases in seeding rates led to declines in yield across all varieties when compared to the optimal rate, with reductions in the Abelina variety ranging from 0.13 to 0.23 tons per hectare, in the Akardia variety from 0.16 to 0.36 tons per hectare, and in the Kyoto variety from 0.22 to 0.46 tons per hectare.